Lifelong effects of prenatal and early postnatal stress on the hippocampus, amygdala, and psychological states of Holocaust survivors - Fňašková, Monika; Říha, Pavel; Nečasová, Markéta; Preiss, Marek; Rektor, Ivan (Scientific reports, 2023)
This study focuses on hippocampal and amygdala volume, seed-based connectivity, and psychological traits of Holocaust survivors who experienced stress during prenatal and early postnatal development. We investigated people who lived in Central Europe during the Holocaust and who, as Jews, were in imminent danger. The group who experienced stress during their prenatal development and early postnatal (PreP) period (n = 11) were compared with a group who experienced Holocaust-related stress later in their lives: in late childhood, adolescence, and early adulthood (ChA) (n = 21). The results of volumetry analysis showed significantly lower volumes of both hippocampi and the right amygdala in the PreP group. Seed-based connectivity analysis revealed increased connectivity from the seed in the right amygdala to the middle and posterior cingulate cortex, caudate, and inferior left frontal operculum in the PreP group. Psychological testing found higher levels of traumatic stress symptoms (TCS-40) and lower levels of well-being (SOS-10) in the PreP group than in the ChA group. The results of our study demonstrate that extreme stress experienced during prenatal and early postnatal life has a profound lifelong impact on the hippocampus and amygdala and on several psychological characteristics.
Keywords: Amygdala; Adolescent; Adult; přežívající; Pregnancy; vitaminy; lidé; Survivors; Humans; Child; Vitamins; Hippocampus; Holocaust; hipokampus; dospělí; holocaust; dítě; amygdala; ženské pohlaví; mladiství; těhotenství; Female